The impact of choice of norms on classification of motor impairment for children born very preterm. (July 2020) - Costa, Raquel; Johnson, Samantha; Cuttini, Marina; Pierrat, Véronique; Sarrechia, Iemke; Barros, Henrique; Zeitlin, Jennifer
Abstract: Background: The Movement Assessment Battery for Children-Second Edition (Movement ABC-2) is widely used to assess children's motor function, yet there is a lack of normative data for many countries. Aims: To assess the extent to which the application of different population reference norms for the Movement ABC-2 affects the classification and prevalence of motor impairment. Design: Data were obtained from two Portuguese regions participating in the Screening to Improve Health in Very Preterm Infants in Europe (SHIPS) Study, which was a five year follow-up of a cohort of children born at <32 weeks' gestation in 2011–2012 in 19 regions in 11 European countries. Perinatal data were extracted from medical records and the Movement ABC-2 was administered at five years of age. Subjects: Of 542 Portuguese children eligible for the five-year follow-up, 413 (76.2%) were evaluated. Outcome measures: Movement ABC-2 raw scores were converted to standardized scores using norms from four countries with national standardisations (UK, Netherlands/Belgium, France and Italy). Results: The prevalence of significant movement difficulties (total score ≤ 5th percentile) was 28.5% using Dutch/Flemish norms, 23.3% using French norms, 16.5% using UK norms and 11.4% using Italian norms; 10.8% and 68.3% of the children were consistently classified as having significant movement difficulties and as not having significant movement difficulties, respectively, according to any norms. However, for 20.9% of children there was a disagreement in motor function status using different norms. Conclusion: The use of different test norms has a large impact on the proportion of children classified with significant movement difficulties, with implications for clinical referrals, healthcare costs and research. Our results underscore the importance of using appropriately validated tests with sound psychometric properties, and raise questions about the large differences in norms for the Movement ABC-2 in European countries. Highlights: The prevalence of significant motor difficulties in very preterm children varied from 11%-29% depending on test norms used. Using different norms, the classification of significant motor difficulties differed for 20% of children. The choice of test norms can have a substantial impact on the classification of motor function